DNA barcoding of spiders from agricultural fields. Issue 2 (3rd July 2019) - Tahir, Hafiz Muhammad; Summer, Muhammad; Mehmood, Sana; Ashraf, Sehrish; Naseem, Sajida
Abstract: In the present study, DNA barcoding was used to assess the percentage accuracy of morphological base identification of spiders from the agriculture fields of district Layyah, Punjab, Pakistan. A total of 872 spiders were captured from June to August of 2017. All the collected spiders were brought to molecular laboratory at GC University Lahore, preserved in 95% ethanol and stored at −20 °C until the DNA extraction. Spiders were evaluated morphologically on the basis of different identification Keys and Catalogs. Morphological identification revealed the presence of 12 families, 29 genra and 49 species. To evaluate the authenticity of morphological identification, tissue samples of 96 specimens were sent to Canadian Center for Biodiversity and Genomics, University of Guelph, Canada. A 658-base pair sequence of COI (Cytochrome c Oxidase Subunit I) of 90 specimens was retrieved successfully, which confirmed the presence of 11 families, 25 genra and 47 species. On the basis of molecular results, all the misidentified specimens were then allotted the correct taxon. Overall accuracy of morphological based identification was 88%. It is concluded from the present study that morphological investigations to identify a spider, are satisfactory but to enhance the accuracy, pace and credibility of results, molecular technique like DNA barcoding is considerable. Furthermore, to magnify authenticity of evaluation of spiders, integrated barcoding- combination of molecular methods and conventional taxonomy- is compulsory.